Relationship of Confidence with Academic Procrastination of Middle School Students and Its Implications in Guidance and Counseling - Hendri Rahmat Saputra; Alizamar Alizamar; Afdal Afdal (Universitas Negeri Padang, 2020)
This research is motivated by the phenomenon of students not completing school work within the deadline due to lack of confidence in their abilities. This type of research is descriptive correlational. The study population numbered 745 students and a sample of 282 students in SMP N 25 Padang. The sampling technique used in this study is Stratified Random Sampling. The instrument used in data collection was a questionnaire of the relationship of confidence with academic procrastination with a choice of Likert scale model answers. Analysis of the data used is descriptive analysis with percentage techniques and to see the relationship between the two variables used statistical analysis with the Pearson Product Moment Correlation technique with the help of the SPSS For Windows 20.0 program. The results of the study revealed that: 1) In general most of the results of the study revealed the confidence of students in SMP Negeri 25 Padang having a moderate level of confidence. 2) Most of the results of the study revealed the academic procrastination of students at SMP Negeri 25 Padang in the medium category. 3) There is a significant negative correlation of self-confidence with students' academic procrastination in SMP Negeri 25 Padang meaning that the higher the level of student's self-confidence, the lower the student's academic procrastination.